Pengalaman Pengobatan Depresi Dengan Nomifensin - R.Soejono Prawirohardjo, R.Soejono Prawirohardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1985)
The paper describes the epidemiology and pathology of depression. The history of therapy against depression and in particular the neurotransmitters hypothesis is presented. A clinical trial was carried out in the Out-Patient Department of the Central General Hospital Dr. Sardjito, Yogyakarta. Twenty depressed patients with ages of 15 Ã¢â¬â 25 years were treated with Nomifensine, during two weeks period, with a daily dose of 50 mg in the morning and 50 mg at noon. Intensity of depression was tested with Hamilton Depression Rating Scale, before treatment, a week after treatment and finally two weeks after. A pairwise retest of differences between two item differences, was chosen for analysis of the means of the initial Ã¢â¬â, mid Ã¢â¬â, and terminal depression intensity. There is a significant decrease in intensity of depression between the initial and terminal evaluation. Remarkable side effects were absent in almost all the patients treated. Nomifensine in daily dose of 2 X 50 mg a day is effective in the treatment of depression. In most instances reduction in total score can be expected within 1 - 2 weeks of drug treatment. Finally, a recommendation is offered. Key Words: nomifensine - depression - neurotransmitters - psychiatry - anti-depressive agents